Improving the Quality of Employees and Members of KSP Tani Makmur: Konsentrasi Sumber Daya Manusia - Rokhimi, Restiana; Nuvriasari, Audita (Asian Journal of Community Services, 2024)
Savings and loan cooperatives or abbreviated as KSP are cooperatives that operate in the field of deposit (savings) and loan (credit) services. KSP Tani Makmur was trusted to manage agribusiness funds and general credit funds for the people of Bantul Regency. This community service is carried out using a method of transferring knowledge with counseling containing motivation and work discipline through making posters in order to increase motivation and enthusiasm at work. The work program implemented can be a solution to increase motivation and work discipline for KSP Tani Makmur.